2015
DOI: 10.5114/wo.2015.54900
|View full text |Cite
|
Sign up to set email alerts
|

Use of the mini-MAC scale in the evaluation of mental adjustment to cancer

Abstract: Aim of the studyThe objective of the study was to evaluate mental adjustment to cancer in patients diagnosed with an oncologic disease through identification of the coping strategies they had adopted.Material and methodsSeventy-four patients of the Clinic of Oncology and Haematology at the Central Clinical Hospital (CSK) of the Ministry of Interior (MSW) in Warsaw were included in the study. The degree of adaptation to cancer was evaluated with the use of the mini-Mental Adjustment to Cancer (mini-MAC) scale. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 6 publications
(10 reference statements)
1
21
0
1
Order By: Relevance
“…Consistent with previous research results, the current study shows that mental adjustment factors including FS or H/H are significantly association with demographic factors such as age, education, marital status, income, and social support variables. 3,4 We observed that younger (<46 years) patients perceived cancer as a challenge and showed significantly increased FS compared with the older (> 46 years) group. Similar findings were noted in a previous study.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Consistent with previous research results, the current study shows that mental adjustment factors including FS or H/H are significantly association with demographic factors such as age, education, marital status, income, and social support variables. 3,4 We observed that younger (<46 years) patients perceived cancer as a challenge and showed significantly increased FS compared with the older (> 46 years) group. Similar findings were noted in a previous study.…”
Section: Discussionmentioning
confidence: 77%
“…The study examined the association between sociodemographic and perceived social support variables in the mental adjustment of patients with breast cancer. Consistent with previous research results, the current study shows that mental adjustment factors including FS or H/H are significantly association with demographic factors such as age, education, marital status, income, and social support variables . We observed that younger (<46 years) patients perceived cancer as a challenge and showed significantly increased FS compared with the older (> 46 years) group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Akceptacja choroby, a także bezpośrednio z nią związanego bólu, cierpienia i dyskomfortu, jest istotną zmienną wykorzystywaną do oceny stopnia przystosowania się pacjenta do sytuacji choroby [3,14,15]. Oznacza uznanie istnienia raka i dostosowanie się do aktualnej sytuacji zdrowotnej, przyjęcie choroby z jej wpływem na różnorodne aspekty funkcjonowania jednostki powiązane nie tylko z kondycją fizyczną, lecz także psychiczną, społeczną, a nawet duchową [16,17].…”
Section: Akceptacja Chorobyunclassified